The Evolution of Representative Claim-Making by the Chinese Communist Party: From Mao to Xi (1949–2019) - Frenkiel, Emilie (2019)
This article traces the evolution of representative claim-making by the Chinese Communist Party (CCP) since the proclamation of the People’s Republic of China in 1949 up to the present day. Based on the analysis of official political discourses on the mass line, the Three Represents and more recent ongoing discourses on digitalization, we demonstrate the change and continuity of claim-making by the CCP. We show that while representative claim-making has undergone a significant transformation from the CCP as the representative of the working class to the sole representative of the Chinese people and nation, the CCP has been consistent throughout decades in maintaining its hegemony over representative claim-making.